Evaluating the Organizational Advancement of Diversity, Equity, and Inclusion in Extension Education - John M. Diaz; Lendel K. Narine; Cody Gusto (Journal of International Agricultural and Extension Education, 2024)
In response to global trends and calls for greater inclusivity, the field of extension education has made significant strides towards embracing Diversity, Equity, and Inclusion (DEI) principles. This study explores the progress of DEI initiatives in the Cooperative Extension System (CES), which has aligned with industry groups, non-profit organizations, academia, and scientific societies worldwide. Through a multifaceted approach, CES has pursued strategies such as intercultural competence (ICC) training for professionals, diversity action plans, and culturally responsive teaching techniques. This study assessed the advancement of DEI in extension education using a survey of DEI specialists across extension organizations in the U.S. Two assessment frameworks guided the study: the Diversity and Inclusion Self-Assessment and the Meyer's DEI Spectrum tool. The results revealed significant variation in the implementation of specific DEI progress indicators, highlighting areas of advancement and opportunities for improvement. Notably, extension organizations demonstrated strong progress in the dimensions of "Data" and "Infrastructure," indicating a commitment to collecting comprehensive demographic data and establishing supportive structures. However, challenges persist, including insufficient administrative support and incomplete organizational commitment. While many organizations have launched initial DEI efforts, sustained progress is essential to ensure the authenticity and effectiveness of these initiatives. The study underscores the importance of continuous assessment and accountability to drive meaningful DEI change within extension organizations. By addressing challenges and building on successes, extension organizations can contribute to a more inclusive and equitable educational landscape that mirrors global aspirations for social justice and diversity.
Keywords: Organizational assessment; Diversity; Equity; Inclusion; Evaluation